OBSERVATIONS ON THE FINE STRUCTURE OF THE DEVELOPING SPERMATID IN THE DOMESTIC CHICKEN - Nagano, Toshio (The Rockefeller University Press, 1962)
The kinetic apparatus, the acrosome and associated structures, and the manchette of the spermatid of the domestic chicken have been studied with the electron microscope. The basic structural features of the two centrioles do not change during spermiogenesis, but there is a change in orientation and length. The proximal centriole is situated in a groove at the edge of the nucleus and oriented normal to the long axis of the nucleus and at right angles to the elongate distal centriole. The tail filaments appear to originate from the distal centriole. The plasma membrane is invaginated along the tail filaments. A dense structure which appears at the deep reflection of the plasma membrane is identified as the ring. The fine structure of the ring has no resemblance to that of a centriole and there is no evidence that it is derived from or related to the centrioles. The tail of the spermatid contains nine peripheral pairs and one central pair of tubular filaments. The two members of each pair of peripheral filaments differ in density and in shape: one is dense and circular, and the other is light and semilunar in cross-section. The dense filaments have processes. A manchette consisting of fine tubules appears in the cytoplasm of the older spermatid along the nucleus, neck region, and proximal segment of the tail. The acrosome is spherical in young spermatids and becomes crescentic and, finally, U-shaped as spermiogenesis proceeds. A dense granule is observed in the cytoplasm between acrosome and nucleus. This granule later becomes a dense rod which is interpreted as the perforatorium.